cblaster: a remote search tool for rapid identification and visualization of homologous gene clusters - Gilchrist, Cameron L M; Booth, Thomas J; van Wersch, Bram; van Grieken, Liana; Medema, Marnix H; Chooi, Yit-Heng (Bioinformatics advances, 2021)
Motivation Genes involved in coordinated biological pathways, including metabolism, drug resistance and virulence, are often collocalized as gene clusters. Identifying homologous gene clusters aids in the study of their function and evolution, however, existing tools are limited to searching local sequence databases. Tools for remotely searching public databases are necessary to keep pace with the rapid growth of online genomic data. Results Here, we present cblaster, a Python-based tool to rapidly detect collocated genes in local and remote databases. cblaster is easy to use, offering both a command line and a user-friendly graphical user interface. It generates outputs that enable intuitive visualizations of large datasets and can be readily incorporated into larger bioinformatic pipelines. cblaster is a significant update to the comparative genomics toolbox. Availability and implementation cblaster source code and documentation is freely available from GitHub under the MIT license (github.com/gamcil/cblaster). Supplementary information Supplementary data are available at Bioinformatics Advances online.